Fundamentals of entrepreneurship (ENT300) : Wahani Noodles Restaurant / Nicodemus Mark Marek ... [et al.] - Mark Marek, Nicodemus; Raya, Nur Khairunnisa Suhada; Anuar, Mohd Haafiz (2018)
WAHANI NOODLES RESTAURANT is a restaurant that sell variety types of noodles from different estate in Malaysia and also from different country in the world. We has an opportunity to generate or maintain our restaurant if it can make customers a reason to come back. A loyalty program that offers discounts to our Facebook/Instagram fans or free meals after a certain number of purchases can cause people to seek out our restaurant instead of just picking the most convenient option. In addition, we will look at the marketplace to assess whether adding product offerings might expand our business well beyond the cost of the additional resources required.